Megölni az evangéliumot? A humanizmus mint kulturális kód - Petneházi, Gábor (Antikvitás & Reneszánsz, 2018)
As paroemium or adagium, the “Evangelia immolare” was invented by Caelius Rhodiginus (Lodovico Ricchieri), who inserted it in his Antiquarum lectionum libri XVI upon Plutarch’s Phocionis vita. Rhodiginus’ monumental collection was in fact faded among Erasmus’ more monumental Adagia, published 8 years earlier as the first edition of Rhodiginus’ Antiquarum lectionum. The peculiar adagium however (translating transitively the verb immolare it’s sense is more than odd) was inserted to the Adagia-collection of Erasmus’ last famulus and pupil, Gilbertus Cognatus, and to that of the Hungarian paroemiographer and historian János Baranyai Decsi. Furthermore, it was reused at the very end of a very specific diplomatic letter of the Polish grand chancellor Jan Zamoyski to the Transylvanian prince Sigismund Báthory in 1593, as a final and encrypted message warning him (like an other Phocion) not to involve into the war against the Turk. Following the way of this particular paroemium (supposedly made up by misreading or misinterpretation) we can detect the linguistic nature of humanism and to measure our boundaries for a genuine comprehension of early modern literary culture in its complexity.